(3QjGV GdfahS aj JUMjM GdCHOGfs - (3GdTjQGRj , ZjGK GdOjf Hf efUhQ GdMSjfj GdTjQGRj,J (B949 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI fSCdc WH bdhHfG ddfLGI eYGde GdTaGA hHYO jbhd dGjNaj Ydi Chdj Gdfgj Cf GdWH ef GdYdhe GdJj jfJaY HgG UGdMI dCf jLYdgG PNjQI dfjd GdfLGI hGdTaGA s
(3BNQgG (B:s
(3ef BNQ GdehLhO jRGO aj GdGTjGA GdeSNfI aj GdTJGA haj GdGTjGA GdeHQOI aj GdUja s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B43s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs